Czynniki chroniące przed samobójstwem młodzieży w wieku 13-19 lat = Factors preventing suicide among youth aged 13-19 - Gmitrowicz, Agnieszka; Wolanek, Urszula; Madej, Agata; Makara-Studzińska, Marta (Journal of Education, Health and Sport, 2015)
Gmitrowicz Agnieszka, Wolanek Urszula, Madej Agata, Makara-Studzińska Marta. Czynniki chroniące przed samobójstwem młodzieży w wieku 13-19 lat = Factors preventing suicide among youth aged 13-19. Journal of Education, Health and Sport. 2015;5(9):671-684. ISSN 2391-8306. DOI10.5281/zenodo.31766 http://dx.doi.org/10.5281/zenodo.31766 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A671-684 https://pbn.nauka.gov.pl/works/642428 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. CZYNNIKI CHRONIĄCE PRZED SAMOBÓJSTWEM MŁODZIEŻY W WIEKU 13-19 LAT FACTORS PREVENTING SUICIDE AMONG YOUTH AGED 13-19 Agnieszka Gmitrowicz1, Urszula Wolanek2, Agata Madej3, Marta Makara-Studzińska3 Klinika Psychiatrii Młodzieżowej CSK IS UM w Łodzi1 Youth Psychiatry Clinic, Central Clinical Hospital, Institute of Dentistry, Medical University of Łódź1 Oddział Psychiatrii Młodzieżowej UM w Łodzi2 Youth Psychiatry Ward, Medical University of Łódź2 Zakład Psychologii Stosowanej UM w Lublinie3 Department of Applied Psychology, Medical University of Lublin3 Streszczenie Wstęp. Zachowania samobójcze stanowią powszechny i poważny problem zdrowotny i społeczny na całym świecie. W literaturze istnieją doniesienia mówiące, iż samobójstwo to jedna z najczęstszych przyczyn zgonów nastolatków w wieku 15-19 lat. Młodzi ludzie dokonują prób samobójczych (PS) będąc pod wpływem następujących czynników: negatywna presja rówieśnicza, wydarzenia o charakterze stresowym, brak umiejętności życiowych. Dlatego też istotne wydaje się poszukiwanie czynników mogących ograniczać to niepokojące zjawisko, do których niewątpliwie zalicza się PS. Cel pracy. Określenie czynników chroniących przed podejmowaniem prób samobójczych (PS) oraz oczekiwań odnośnie skutecznej pomocy po PS. Materiał i metoda. W badaniu udział wzięło 80 pacjentów w wieku 13-19 lat. Narzędzie badawcze stanowił kwestionariusz ankiety własnego autorstwa. Uzyskane wyniki poddano analizie procentowej. Wyniki. Co trzeci badany nastolatek swoje problemy omawiał wspólnie z rówieśnikami, natomiast tylko co ósmy badany mógł liczyć na pomocy ze strony rodziców. Oczekiwania pacjentów w zakresie otrzymywania pomocy jako formy zapobiegania przed PS dotyczą głównie ich relacji rodzinnych. Oczekują oni również zmian w systemie leczenia. Wnioski. Badani potrzebują czuć się kochani, bezpieczni, mieć wsparcie ze strony rodziców oraz rówieśników. Chcą mieszkać w domach rodzinnych. Nie chcą być obiektami przemocy, być źle traktowanymi przez innych oraz wychowywać się w patologicznym środowisku. Potrzebują zwiększenia poczucia własnej wartości i zaakceptowania siebie. Słowa kluczowe: psychiatria, młodzież, próby samobójcze, czynniki ochronne, samobójstwo. Abstract Introduction. Suicidal behavior is a common and serious health and social problem worldwide. In the literature there are reports stating that suicide is one of the most common causes of death among teenagers aged 15-19. Young people make suicidal attempts (SA) when influenced by the following factors: negative peer pressure, events of stress, lack of life skills. Therefore, it seems important to search for factors that may limit this disturbing phenomenon, in which SA is undoubtedly included. Aim of the study. The aims are to determine the protective factors preventing suicide attempts (SA) and develop expectations for effective assistance after SA. Materials and methods. The study involved 80 patients aged 13-19. The research tool was a questionnaire of own authorship. The results were subject to percentage analysis. Results. Every third teenager respondent discussed their problems with their peers, while only every eighth respondent could count on help from parents. Patients’ expectations in terms of receiving aid as a form of prevention against SA relate mainly to their family relations. They also expect changes in the system of treatment. Conclusions. Respondents need to feel loved, safe and having support from parents and peers. They want to live with their families. They do not want to be objects of violence, be badly treated by others and grow up in a pathological environment. They need increasing self-esteem and self-acceptance. Keywords: psychiatry, youth, suicidal attempts, suicide.